Sguardi in conflitto: scrittura femminile e memoria collettiva nel documentario italiano contemporaneo (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
This article aims to analyse how, in recent decades, the documentary has been the preferred space for the affirmation of new female voices in Italy, especially through the use of hybrid practices that include the combination of found footage, amateur film, and home movie. While the contemporary audio-visual scenario is increasingly shifting to autobiography, female writing in Italian documentaries participates in the same focus on subjectivity, nevertheless as an “intersubjective” construction. Autogynography structures relational writing, in which the “we” of the narrator's voice has the primary purpose of building a collective identity, rather than affirming a singularity as in the conventional autobiography.
Keywords: Autobiography; Italian cinema; self-representation; archive; gender